Local traditional foods contribute to diversity and species richness of rural women's diet in Ecuador - Penafiel, Dolores; Cevallos-Valdiviezo, Holger; Espinel, Ramón; Van Damme, Patrick (Public health nutrition, 2019)
OBJECTIVE: To evaluate the dietary diversity and the nutrient contribution of traditional foods (locally cultivated and wild) by conducting a food intake study in rural Ecuador. DESIGN: Repeated 24 h recalls over a 14 d interval and frequency of consumption served to simulate the usual diet by the Multiple Source Method. Data on missing visits (n 11) were imputed using multivariate imputation by chained equations. The intakes of three macro- and six micronutrients were reported. Nutrient Adequacy Ratios, Mean Adequacy Ratio (MAR), Dietary Species Richness (DSR) and Minimum Dietary Diversity for Women were used as measures of dietary quality. A linear quantile mixed model was used to investigate the association between DSR, local species, MAR, age, education and occupation. SETTING: Guasaganda, Cotopaxi (Ecuador). PARTICIPANTS: Rural, indigenous adult women, non-pregnant and not breast-feeding. RESULTS: The studied diet had MAR of 0·78. Consumption of traditional foods contributed 38·6 % of total energy intake. Daily requirements for protein, carbohydrates, Fe and vitamin C were reached. An extra level of consumption of local species was associated with an increase in median MAR for macronutrients of 0·033 (P < 0·001). On the other hand, an extra level of consumption of local species was associated with an increase in median MAR for micronutrients of 0·052 (P < 0·001). CONCLUSIONS: We found statistical evidence that traditional foods contribute to adequate intakes of macro- and micronutrients and dietary diversification in the studied population. Future public health interventions should promote the cultivation and consumption of traditional foods to increase the quality of the local diet.
Keywords: dospělí; ovoce; venkovské obyvatelstvo; Humans; lidé středního věku; Ekvádor; zelenina; Middle Aged; dieta - přehledy; mladý dospělý; Nutritional Status; Diet Surveys; Rural Population; Vegetables; Ecuador; Adult; Diet; Adolescent; nutriční stav; ženské pohlaví; lidé; mladiství; dieta; Aged; Fruit; senioři; Young Adult; Female